Breeding of the Eurasian Scops Owl (Otus scops) in northern Slovakia - Radoslav Michalec; Dušan Karaska (Tichodroma, 2022)
The first documented nesting of the Eurasian Scops Owl (Otus scops) in northern Slovakia (Oravice area in the Western Tatras in 2021) is described. The nest was found in an occupied former woodpecker nest cavity and a fledgling was observed. All known observations of the species in northern Slovakia to date are summarized and the species range and population trends in Europe are discussed. This breeding may be related to the increase of the European population and the northward expansion of the species.